Reflections on Political Ecology of Mount Cameroon’s Prunus Africana - Nebasifu, Ayonghe Akonwi (Advances in Social Sciences Research Journal, 2018)
This paper written for World-Ecology Research Network Conference at University of Helsinki, August 2018, reflects upon developments in capitalism of Prunus Africana within a theoretical framework of co-management critique. On the case of Mount Cameroon in Sub-Saharan West Africa, I argue processes of commercialization and socio-economic repercussions surrounding Prunus Africana: a plant that serves for treatment of prostatic diseases – interwoven with bureaucratic initiatives of sustainable management. By reviewing published literature, I argue the involvement of stakeholders in capitalist arrangements from the 1990s to periods following the establishment of Mount Cameroon National Park – significantly scrutinized by Convention on International Trade in Endangered Species (CITES), European Commission, and the International Union for Conservation of Nature (IUCN). Major actors include Mount Cameroon Prunus Management Company (MOCAP) endorsed by the state; state subsidiaries Cameroon Development Corporation (CDC) and Limbe Botanic Garden (LBG); collaborate buyers – Plantecam and Afriquia Medicament (AFRIMED); and Prunus Africana Harvesters’ Unions in nearby villages. Analysis demonstrate benefits in sustainable harvesting of Prunus, whilst raising ontological concerns of resource-appropriation, elite control, unsatisfactory labour wages, and vulnerabilities of traditional ecological knowledge to commercialization.